COMPARATIVE ANALYSIS OF PROFITABILITY BETWEEN BEFORE AND DURING PANDEMIC COVID-19 IN THE COMPANY SECTOR FOOD AND BEVERAGES ARE LISTED IN INDONESIA STOCK EXCHANGE - Giovani, Radju; Aminuddin, Rais Hilmi; Alfaridzky, Muhammad; Putri, Fernanda Lovita; Aquilera, Leona; Bayunitri, Bunga Indah (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to comparative analysis of profitability between before and during pandemic covid-19 in the company sector food and beverages are listed in Indonesia Stock Exchange. The financial ratios used in this study are Net Profit Margin, Return on Assets and Return on Equity. The population in this study are public companies listed on the Indonesia Stock Exchange for the period of Quarter 1 of 2019 to Quarter 3 of 2020. Sampling was carried out by purposive sampling method so that 13 companies were obtained as samples. The data analysis method used in this study uses quantitative descriptive analysis testing by describing or describing the data that has been collected. The results of data analysis show that there is a significant comparison to several ratios,the net profit margin decreased by -25%, the return on assets decreased by -10.8%, and the return on equity increased by 31.95%. These results were obtained before and during the COVID-19 pandemic from each company.